A synthesis on SWOT analysis of public sector healthcare knowledge management information systems in Pakistan - Arshad, Arfan; Noordin, Mohamad Fauzan; Othman, Roslina (The Science and Information (SAI) Organization, 2017)
Healthcare is a community service sector and has been delivering its services for the betterment of civic health since its establishment at communal level. For working efficiently and effectively, this sector profoundly relies on correct and complete health information of people and a proficient integrated healthcare knowledge management information system (HKMIS) to manage this information. The performance of Healthcare organizations has significantly augmented by inception of Information and Communications Technology (ICT) in HKMIS in developed countries, but is yet to exhibit its full potential in developing countries specifically those with huge populations like Pakistan. An exploratory qualitative research methodology was adopted to conduct this study. The purpose and objective of this study was to determine and investigate the internal and external factors that influence the performance of HKMIS by performing SWOT analysis on two of the largest public-sector healthcare organizations of Pakistan. The findings of this study will certainly help authorities to devise methods of improvement in Pakistani HKMIS eventually paving ways towards a better and improved healthcare in the future.